Proses Hydrotest pada Tube Bundle Pertamina RU III Plaju Palembang di PT. PAL Indonesia - Dimas Nur Isa Prahesti; Arsana, I Made; Yunus, Yunus (Universitas Nusantara PGRI Kediri, 2023)
A tube bundle (shell and tube heat exchanger type) is a tool to transfer heat from a fluid system that usually functions as a cooler or heater. So, to find out if the tool can function properly it is necessary to hold a test, one of which is a hydrotest. Hydrotest is a test method to measure the strength and detect leaks in piping systems. This test is very important to do to ensure there are no leaks in the tube bundle. The test method uses water as a fluid medium which is filled into the tube bundle and is pressured by a hydrostatic test pump at not less than 1.5 times the nominal pressure. In this test, the tube bundle being tested has a nominal pressure of 183.95, so it must be tested with a pressure of 367.91 PSIG. After checking, there was no pressure drop from the hydrostatic test pump. The graph on the pressure recorder is as desired so that this test is declared to have passed. The tube bundle that is declared to have passed the hydrotest will then proceed to the final check stage by the QA officer. When doing a hydrotest, it must be done carefully because if you experience overpressure it can cause fatality in the tube bundle and damage to facilities.